(untitled) - Gilman, John J. (Cambridge, 2003)
Requiring knowledge of the chemistry and physics of materials, this study relates the complete set of strength characteristics of constituent atoms to their electronic structures. The book uses classical and quantum mechanics (since both are needed to describe these properties) and begins with short reviews of each area. After the reviews, the three major branches of the strength of materials are divided into the following sections: the elastic stiffnesses; the plastic responses; and the nature of fracture.
Keywords: Strength of materials,Electronic structure